Proceedings of the 1st International Conference on Social Sciences and Interdisciplinary Studies (ICSSIS 2018) 2019
DOI: 10.2991/icssis-18.2019.33
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of NDVI Change To Spatial Distribution Of Land Surface Temperature (A Study in Medan City, Indonesia)

Abstract: This study aims to determine: (1) spatialtemporal variations in land surface temperature in Medan City, (2) spatial-temporal variations in vegetation index values (NDVI) in Medan City, (3) the relationship between LST and NDVI in Medan City. The design of this research is correlational and population research conducted with a spatial and temporal approach to analyse data spatially in different years of image recording. The variables in this study are land surface temperature and vegetation density. Data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…& Technol. 28 (4): 1517-1529 Vegetation or healthy plants in an area were affected by LST variation (Rahmad et al, 2019). Two studies reported on the increasing rate of forest conversion in the areas of Papua New Guinea and Papua (Alamgir et al, 2019;Austin et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…& Technol. 28 (4): 1517-1529 Vegetation or healthy plants in an area were affected by LST variation (Rahmad et al, 2019). Two studies reported on the increasing rate of forest conversion in the areas of Papua New Guinea and Papua (Alamgir et al, 2019;Austin et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the distribution of temperatures by pixels. LST classes can also exhibit a spatial-temporal distribution (Rahmad et al, 2019). A study in South Tangerang, a region with the highest population growth in the Banten province of Indonesia, showed that the LST has increased 0.4-0.7 o C per year, mainly due to housing growth and decrease vegetation density (Oktavianingrum et al, 2020).…”
Section: Introductionmentioning
confidence: 99%